Supporting and Hindering Factors Associated with COVID-19 Health Protocol Adherence Among Online Motorcycle Taxi Riders in Samarinda City, Indonesia - Setyowati, Dina Lusiana; Asrianti, Tanti; Kamba, Ismail; Agustini, Rina Tri (Kesmas, 2025)
The COVID-19 pandemic has underscored the importance of preventive health protocols, especially for high-contact occupations, such as online motorcycle taxi riders. However, adherence among these riders is inconsistent, particularly in economically constrained regions, such as Samarinda, a buffer zone for Indonesia's new capital. This study examined the influence of supporting and hindering factors on COVID-19 protocol compliance. A cross-sectional design was employed with 87 riders selected through quota sampling. Data were collected using structured questionnaires and analyzed using Spearman's rank correlation to assess the relationships between influencing factors and compliance levels. Economic barriers, especially high personal protective equipment (PPE) costs (46%), hindered protocol adherence, whereas supporting factors such as leadership and workplace-provided PPE showed no statistically impact on compliance. This finding suggested that financial constraints were the primary barrier, outweighing institutional support. Therefore, targeted financial assistance and strengthened public health policies are recommended to improve compliance. Enhancing community-level awareness and providing PPE subsidies could reinforce adherence and reduce transmission risk in high-contact occupations.